2006
DOI: 10.1136/thx.2005.042275
|View full text |Cite
|
Sign up to set email alerts
|

Survival impact of epidermal growth factor receptor overexpression in patients with non-small cell lung cancer: a meta-analysis

Abstract: Background: It is thought that overexpression of epidermal growth factor receptor (EGFR) in non-small cell lung cancer (NSCLC) might compromise patient survival, presumably by promoting tumour growth by an autocrine mechanism. However, conflicting results have been reported from various laboratories, and the clinical importance of EGFR overexpression remains unsettled. Methods: A meta-analysis of previous studies was performed to quantitatively review the effects of EGFR overexpression on survival in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 60 publications
8
56
3
1
Order By: Relevance
“…EGFR protein overexpression was found in 35 of 42 nonadenocarcinoma NSCLCs (83%). Patients in our cohort thus showed a higher frequency of EGFR protein overexpression than those in a previous meta-analysis, 28 which may be because of differences in ethnicity. Whereas we have previously reported that EGFR overexpression is strongly correlated with TKD mutations in adenocarcinomas, 23 no such correlation was demonstrated in the present study for nonadenocarcinoma NSCLCs.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…EGFR protein overexpression was found in 35 of 42 nonadenocarcinoma NSCLCs (83%). Patients in our cohort thus showed a higher frequency of EGFR protein overexpression than those in a previous meta-analysis, 28 which may be because of differences in ethnicity. Whereas we have previously reported that EGFR overexpression is strongly correlated with TKD mutations in adenocarcinomas, 23 no such correlation was demonstrated in the present study for nonadenocarcinoma NSCLCs.…”
Section: Discussioncontrasting
confidence: 38%
“…28 For EGFR Western blotting analysis, 100 lg of tumor or normal lung protein was used. Protein samples were subjected to Western blotting analyses using anti-EGFR polyclonal antibody (Santa Cruz Biologicals, Santa Cruz, CA) according to the manufacturer's instructions.…”
Section: Western Blottingmentioning
confidence: 99%
“…Some data have showed that EGFR expression in pancreatic cancer does not reflect the prognosis of patients [10,11]. Accurate and conclusive evaluation of the clinical significance of EGFR expression is important to pancreatic cancer for choosing appropriate future molecular targets [17]. Therefore, we have carried out a meta-analysis of the literature to quantitatively assess the prognostic significance of EGFR expression on survival in patients with pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Increased EGFR expression was considered to be a poor prognostic factor in NSCLC patients 12,13 but a meta-analysis combining 18 studies of 2972 patients did not confirm the prognostic significance of EGFR expression (HR=1.14; 95% CI 0.97-1.34; P=0.103) (ref. 14 ). The predictive value of EGFR amplification/overexpression for responsiveness to EGFR tyrosine kinase inhibitors (EGFR TKIs) was tested in several studies.…”
Section: Amplification/overexpressionmentioning
confidence: 99%